Cult of the State in “New Turkey” - Chudziak, Mateusz (Sensus Historiae, 2022)
In the Turkish Republic, as a result of deliberate break from the Ottoman heritage, a nationalist ideology was developed that legitimized new revolutionary order. The state, powerful and overwhelming in its institutional dimension, became equally overwhelming in the symbolic one. In this way, it created, developed, and propagated its own myth. Kemalist Turkey was contested by various circles, but the undermining of its ideological foundations came only as a result of the new post-2002 revolution. It resulted in the creation of the so-called “New Turkey” - a thoroughly reconstructed state. Apart from institutions, the reconstruction also affected the symbolic sphere – as part of the neo-Ottoman project, aimed to create a national community anew, the reputation of the Ottoman Empire was restored, and Islam was openly declared a key and fundamental component of Turkishness. However, many elements of Kemalist mythology were not rejected – the Turkish myth of the state was renewed and complemented with Islamic and Ottoman themes. As a result, “New Turkey” developed a republican cult of the state, synthesizing the elements of old Kemalist ideology and neo-Ottomanism promoted by new authorities.